Ethical dilemmas and validity issues related to the use of new cooling technologies and early recognition of exertional heat illness in sport - Douglas J Casa; Yuri Hosokawa; Kumpei Tanisawa; Borja Muniz-Pardos; Yannis P Pitsiladis; Fumihiro Yamasawa; Konstantinos Angeloudis; Fergus M Guppy; Garrett I Ash; Andrew J Grundstein (BMJ Open Sport & Exercise Medicine)
The Tokyo 2020 Olympic Games is expected to be among the hottest Games in modern history, increasing the chances for exertional heat stroke (EHS) incidence, especially in non-acclimatised athletes/workers/spectators. The urgent need to recognise EHS symptoms to protect all attendees’ health has considerably accelerated research examining the most effective cooling strategies and the development of wearable cooling technology and real-time temperature monitoring. While these technological advances will aid the early identification of EHS cases, there are several potential ethical considerations for governing bodies and sports organisers. For example, the impact of recently developed cooling wearables on health and performance is unknown. Concerning improving athletic performance in a hot environment, there is uncertainty about this technology’s availability to all athletes. Furthermore, the real potential to obtain real-time core temperature data will oblige medical teams to make crucial decisions around their athletes continuing their competitions or withdraw. Therefore, the aim of this review is (1) to summarise the practical applications of the most novel cooling strategies/technologies for both safety (of athletes, spectators and workers) and performance purposes, and (2) to inform of the opportunities offered by recent technological developments for the early recognition and diagnosis of EHS. These opportunities are presented alongside several ethical dilemmas that require sports governing bodies to react by regulating the validity of recent technologies and their availability to all.